Legal Comparison Between Singapore and Indonesia in Traffic Regulation - Yunita Adinda Wulandari (Proceedings Series on Social Sciences & Humanities, 2023)
Traffic is defined as the movement of vehicles and people in the Road Traffic Space, while what is meant by the Road Traffic Space is infrastructure intended for the movement of vehicles, people and/or goods in the form of roads and supporting facilities. The research method used is descriptive qualitative in nature. The results of his research are the differences in Traffic regulations, namely having different laws. One striking difference is regarding seat belts. Singapore is all about wearing seat belts. In Indonesia, the use of seat belts is not mandatory for passengers in the back. Meanwhile, in Singapore, all passengers in motorized vehicles are required to wear seat belts, both in front and behind. This difference in traffic regulations can affect the level of safety in driving in both countries. In addition, differences in traffic law regulations can also affect the actions taken in handling traffic violations. In Indonesia, traffic violations are generally dealt with by paying fines only, whereas in Singapore traffic violations can be punished with larger fines or even imprisonment. In his research results, in Singapore, motorized vehicles must pass emission tests every two years, while in Indonesia emission tests are only required every five years. This can affect air quality in both countries. From these differences, it is important to study traffic law comparisons between Indonesia and Singapore. This comparison can provide an overview of the advantages and disadvantages of each traffic regulation system, as well as provide inspiration for the development of better traffic regulations in the future.